The Hidden Pathos Behind the Refrain “Two Leaves and A Bud” - Smt. , S. Sailaja (International Journal of Psychosocial Rehabilitation, 2014)
The present paper aims at - how the word “refrain” plays a vital role in Mulkraj Anand’s Novel “Two Leaves and a Bud”. According to grammar, the word “refrain” has two lexical performances: As a Noun and As a verb - as a noun the word means: “a phrase or a verse recurring at intervals in a song or poem, especially at the end of each stanza in chorus.” - as a verb the same word means: “stop oneself from doing something.” The novel “Two Leaves and a Bud” takes its title from the simple refrain which the tea leaves gatherers, at the Macpherson Tea Estate in Assam, recite as they pick two leaves and a bud: I will make a sheaf Plucking, plucking, plucking Two leave and a bud Two leave and a bud The workers at the workplace sing this type of refrain for getting rid of tiredness. But the hidden pathos behind the refrain makes the workers refrain from thinking of their own welfare, human justice as well as human rights. It is an attempt to show the pathetic conditions of the Indian labourers at the tea estates; how they are, brutally, exploited by the rulers and also why the poor workers at the tea plantation refrain from protesting against injustice and inhumanity instead of enjoying themselves by singing the refrain at work